Semi-permeable membrane as well as preparation method and application thereof

By providing a modified active layer on the porous support layer of the semipermeable membrane, and modifying dendritic polyamine compounds and strong negative group, the problems of wide pore size distribution and insufficient selection separation performance of the existing semipermeable membrane are solved, and efficient monovalent and multivalent ion separation performance is achieved.

CN119707029APending Publication Date: 2025-03-28TORAY ADVANCED MATERIALS RES LAB CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311264411.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing semipermeable membranes have shortcomings in the selection separation performance of monovalent/multivalent metal ions, mainly due to problems such as incomplete monomer reaction and wide pore size distribution.

Method used

By providing a modified active layer on the porous support layer, the modified active layer includes a primary layer containing a dendritic polyamine compound and a negatively charged layer containing a strongly negatively charged group formed on the primary layer, thereby adjusting the pore size distribution and improving the surface load density.

Benefits of technology

The uniformity of the pore size distribution of semipermeable membranes and the improvement of surface negative charge density are achieved, which significantly improves the selection separation performance of monovalent and multivalent ions, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004475378540000131
    Figure BDA0004475378540000131
  • Figure BDA0004475378540000171
    Figure BDA0004475378540000171
Patent Text Reader

Abstract

The invention relates to a semipermeable membrane and a preparation method and application thereof. The semipermeable membrane comprises a porous support layer and a modified active layer arranged on the porous support layer, the modified active layer comprises a dendritic polyamine compound, a primary layer formed by polyamine and polyacyl chloride, and a negatively charged layer which is formed on the primary layer and contains strong negatively charged groups. The semipermeable membrane has relatively high monovalent / multivalent metal ion selective separation performance, and can realize efficient separation of different metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a semipermeable membrane and a preparation method and application thereof. Background Art

[0002] Membrane water treatment is an important water treatment process that can be used in water treatment, food industry, pharmaceutical industry and other fields. Its core is the semipermeable membrane, and the performance of the semipermeable membrane greatly affects the effect of its application. The performance of the semipermeable membrane mainly depends on the structure and properties of its active layer. The active layer is usually composed of polyamide and is formed on a porous support layer by interfacial polymerization. Interfacial polymerization is a simple, efficient and controllable membrane preparation method. It uses two immiscible monomer solutions to undergo polymerization reaction at the interface of the porous support layer to form an ultra-thin polymer film. The semipermeable membrane prepared by interfacial polymerization has good mechanical strength, chemical stability and separation performance, but it also has some disadvantages, such as the rough surface of the active layer and the wide pore size distribution. These disadvantages will affect the monovalent / divalent metal ion selective separation performance of the semipermeable membrane.

[0003] In order to improve the monovalent / divalent metal ion selective separation performance of the semipermeable membrane, some methods have been proposed, such as changing the monomer concentration, adding additives, adjusting the pH value, controlling the reaction time, etc. Among them, adding additives is a commonly used method, which can adjust the ion selective separation performance of the semipermeable membrane by changing the structure and properties of the active layer. For example, quaternary ammonium salt compounds or nanoparticles are added to the aqueous phase of polyamine to change the charge properties of the semipermeable membrane surface, so that the membrane surface is positively charged, so as to improve the monovalent / polyvalent ion selective separation performance when applied in fields related to metal ion separation.

[0004] However, existing improvement methods also have some problems, such as difficulty in controlling the concentration of additives, damage to the porous support layer by additives, incomplete reaction between monomers, and wide pore size distribution of the semipermeable membrane, which results in insufficient selectivity of the semipermeable membrane for monovalent / polyvalent ions. Summary of the invention

[0005] The technical problems to be solved by the present invention are:

[0006] The purpose of the present invention is to solve the problems of incomplete reaction between monomers and wide pore size distribution of semipermeable membranes in the prior art, and to provide a semipermeable membrane and a preparation method and application thereof. The semipermeable membrane has high monovalent / polyvalent metal ion selective separation, can achieve efficient separation of monovalent and polyvalent ions, and has a simple and easy preparation process, high reaction efficiency, and is suitable for large-scale industrial production.

[0007] The means for solving the above-mentioned technical problems of the present invention are:

[0008] After repeated studies, the inventors of the present invention found that by setting a modified active layer on the porous supporting layer of the semipermeable membrane, the modified active layer includes a primary layer containing a dendritic polyamine compound and a negatively charged layer containing a strong negatively charged group formed on the primary layer, thereby making the pore size of the semipermeable membrane smaller and the pore size distribution uniform. At the same time, through the modification of the strong negatively charged groups, the surface load electric density is increased and the charge negativity is strengthened, which has the advantage of high selectivity for monovalent and polyvalent ions, thereby achieving the purpose of efficient separation of monovalent and polyvalent ions.

[0009] The present invention provides a semipermeable membrane, comprising a porous support layer and a modified active layer arranged on the porous support layer, wherein the modified active layer comprises a primary layer containing a dendritic polyamine compound and a negatively charged layer containing a strong negatively charged group formed on the primary layer. The "dendritic polyamine compound" is a compound having a dendritic structure, which is a hyperbranched structure formed by repeating and linearly connecting oligomers through branching units, and the terminal group is a primary amine group.

[0010] Preferably, the dendritic polyamine compound is one or more of polyamide amine, polylysine or polypropylene imine. Since the amino group specific density of the aforementioned dendritic polyamine compound will change with the number average molecular weight, thereby affecting the regulation effect during interfacial polymerization, it is further preferred that the number average molecular weight of the aforementioned dendritic polyamine compound is 400Da-10000Da, and the corresponding dendritic polyamine molecules are dendritic polyamine molecules of the 0th to 3rd generations. When the molecular weight exceeds 10000Da, the specific density of the amino group will gradually decrease, which will lead to an increase in the defects of the semipermeable membrane. When the molecular weight is less than 400Da, the demulsification effect is poor, which will lead to an increase in the defects of the semipermeable membrane. Since polyamide amine has a more optimal spatial structure, it has a better effect of emulsification and regulation of interfacial polymerization reaction, so it is more preferred that the aforementioned dendritic polyamine compound is a 0th to 3rd generation polyamide amine dendrimer.

[0011] The negatively charged layer of the aforementioned semipermeable membrane is preferably obtained by reacting a primary layer with a compound containing an amino group and at least one of the strongly negatively charged groups.

[0012] The compound containing an amino group and at least one of the strongly negatively charged groups of the aforementioned semipermeable membrane is preferably a small molecule compound containing at least one amino group connected to a carbon atom and at least one of the strongly negatively charged groups. Preferably, the small molecule compound preferably includes a compound having the following chemical formula:

[0013] R a (Ch an ) b NH m

[0014] Wherein R is the strong negative charge group, the strong negative charge group is a sulfonic acid group or a phosphoric acid group; a is any integer from 1 to 3, b is any integer from 1 to 10, n is any integer from 0 to 2, and m is any integer from 1 to 2. According to the reactivity of the small molecule, the preferred small molecule compound is one or more of 2-aminoethanesulfonic acid, 3-amino-1-propanesulfonic acid, N-methyltaurine, (1-aminoethyl)phosphonic acid, 3-aminopropylphosphoric acid and the corresponding salt compounds thereof.

[0015] Preferably, the average pore size of the modified active layer of the aforementioned semipermeable membrane is A, and the proportion of pores with a pore size > 1.5 A is ≤ 15%. When the content of macropores > 1.5 A is greater than 15%, the monovalent / divalent ion selective separation of the semipermeable membrane will be reduced.

[0016] The modified active layer surface contains carboxyl groups, and the relationship between the number C of the aforementioned carboxyl groups and the total amount X of the strongly negatively charged groups is C / X≤1.5.

[0017] The negative charge group density on the surface of the semipermeable membrane is measured by toluidine blue staining method, and the negative charge group density represents the amount of negative charge groups per unit area on the surface of the semipermeable membrane. The surface negative charge group density of the modified active layer of the aforementioned semipermeable membrane is ≥ 20 / nm -2 When the surface negative charge group density of the modified active layer is less than 20 / nm -2 When , the charge effect is small, which is not conducive to improving the monovalent / divalent ion selectivity.

[0018] The present invention also provides a method for preparing a semipermeable membrane, comprising the following steps:

[0019] (1) contacting the porous support layer with an aqueous solution containing a dendritic polyamine compound and a polyamine monomer, and then contacting the porous support layer with an oily solution containing a polyacid chloride to form a primary layer on the porous support layer; (2) contacting the primary layer with a solution of a compound containing an amino group and at least one strongly negatively charged group to obtain a semipermeable membrane containing a modified active layer.

[0020] The material of the aforementioned porous support layer preferably includes one or more of polysulfone, polypropylene or polyacrylonitrile.

[0021] The aforementioned polyamine preferably includes one or more of aromatic polyamine, aliphatic polyamine or alicyclic polyamine, and further preferably, the polyamine is methylenedianiline, polyethylene glycol diamine, N,N-dimethyl-m-phenylenediamine, tetraethylenepentamine, triethanolamine, m-phenylenediamine, s-phenylenediamine, p-phenylenediamine, polyetheramine, dodecylamine, diisobutylamine, 3-fluoroaniline, 3-chloroaniline, heptylamine, cycloheptylamine, piperazine, 3-aminopiperazine, n-hexylamine and decylamine. According to the structure of the active layer formed, more preferably, the polyamine may include one or more of m-phenylenediamine, tetraethylenepentamine or piperazine.

[0022] The aforementioned dendritic polyamine compound comprises one or more of polyamidoamine, polylysine or polypropyleneimine. Since the amino group density of the dendritic polyamine compound varies with the number average molecular weight, preferably, the dendritic polyamine compound is one or more of the 0th to 3rd generation, and the number average molecular weight is 400Da-10000Da. Since polyamidoamine has a more perfect hyperbranched spherical structure and has a better effect of regulating the interfacial polymerization reaction, more preferably, the dendritic polyamine compound is one or more of the 0th to 3rd generation polyamidoamine.

[0023] The mass fraction of the polyamine in the aforementioned aqueous phase is 0.1wt%-3wt%. If the content of the polyamine is too high, the flux of the semipermeable membrane will be sharply reduced, and if it is too low, the defects of the semipermeable membrane will increase.

[0024] The mass concentration of the dendritic polyamine compound in the aqueous solution is less than or equal to 10% of the mass concentration of the polyamine monomer. Too high a content will lead to a significant increase in the defects of the semipermeable membrane. Preferably, the mass fraction of the dendritic polyamine compound is ≤0.3wt%.

[0025] The aforementioned polyacyl chloride preferably includes one or more of aromatic polyacyl chloride or aliphatic polyacyl chloride, and the polyacyl chloride is further preferably one or more of biphenyl dichloride, trimesoyl chloride, benzoyl chloride, terephthaloyl chloride, isophthaloyl chloride, phthaloyl chloride, oxalyl chloride, benzene disulfonyl chloride, cyclopentane dichloride, cyclopentane trichloride, cyclohexane trichloride, succinyl chloride, succinyl chloride, glutaric trichloride, glutaric chloride, hexachlorotrichloride, hexachlorotrichloride, cyclopentane tetrachloride, cyclohexane dichloride, sebacoyl chloride, sebacotrichloride, tetrahydrofuran dichloride, tetrahydrofuran tetrachloride, cyclopropane trichloride, cyclobutane dichloride, cyclobutane tetrachloride and cyclohexane tetrachloride. It is more preferred that the polyacyl chloride is at least one of trimesoyl chloride or adipic chloride by the structure of the formed active layer.

[0026] The mass fraction of the polyacid chloride in the aforementioned oil phase is 0.01wt%-0.5wt%.

[0027] The aforementioned compound containing an amino group and at least one of the strongly negatively charged groups is a small molecule compound containing at least one amino group connected to a carbon atom and the strongly negatively charged group. Preferably, the small molecule compound preferably includes a compound having the following chemical formula:

[0028] R a (ch in ) b NH m

[0029] Wherein R is the strong negative charge group, the strong negative charge group is a sulfonic acid group or a phosphoric acid group, a is any integer from 1 to 3, b is any integer from 1 to 10, n is any integer from 0 to 2, and m is any integer from 1 to 2. According to the reactivity of the small molecule, the more preferred small molecule compound is one or more of 2-aminoethanesulfonic acid, 3-amino-1-propanesulfonic acid, N-methyltaurine, (1-aminoethyl)phosphonic acid, 3-aminopropylphosphoric acid and the corresponding salt compounds thereof.

[0030] Preferably, the mass concentration of the compound solution containing an amino group and at least one of the strongly negatively charged groups is ≤20wt%. Since the reaction is more complete at a higher concentration, the mass concentration of the compound solution containing an amino group and at least one of the strongly negatively charged groups is further preferably 10wt%-20wt%.

[0031] The reaction temperature when the solution of the compound containing an amino group and at least one strongly negatively charged group contacts the primary layer is preferably 20° C. to 85° C. Since the higher the reaction temperature, the stronger the reaction activity, and the more intense the molecular thermal motion, the more strongly negatively charged groups are introduced, it is further preferred that the reaction temperature when the solution of the compound containing an amino group and at least one strongly negatively charged group contacts the primary layer is 45° C. to 85° C.

[0032] The present invention also provides an application of a semipermeable membrane in the recovery of cathode materials of waste lithium batteries, thereby achieving efficient separation and concentration of cathode lithium and other multivalent metals of the battery.

[0033] The specific effects are as follows:

[0034] The dendritic polyamine compound added to the water phase of the present invention has the functions of demulsification, stabilization and the like of a surfactant because it contains lipophilic groups and hydrophilic groups, and can improve the migration rate of monomers during interfacial polymerization, improve the interfacial polymerization reaction, and form a semipermeable membrane with uniform pore size distribution; at the same time, because it contains a large number of amino groups, it can also participate in the interfacial polymerization reaction as a reaction monomer, thereby improving hydrophilicity and chargeability.

[0035] Furthermore, the present invention uses a compound containing an amino group and at least one of the strong negatively charged groups to react with the primary active layer formed by the above-mentioned interfacial polymerization, and modifies the surface of the active layer with the strong negatively charged groups, so that the surface of the active layer contains a large number of the strong negatively charged groups; at the same time, because the amino group of the dendritic polyamine compound contained in the polyamide active layer carries a strong positive charge, it will generate charge attraction with the strong negatively charged group, thereby attracting the compound containing an amino group and at least one of the strong negatively charged groups, and further reducing the pore size and pore size distribution of the semipermeable membrane.

[0036] The semipermeable membrane of the present invention has the characteristics of narrow pore size distribution and strong load capacity, and has good ion selective separation. When applied to the metal recovery process of waste batteries, the removal rate of lithium metal ions is less than 50%, and the removal rate of other multivalent metal ions is greater than 99%, which can achieve efficient separation of lithium metal ions from other multivalent metal ions. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0038] The test conditions and test methods of each parameter in the embodiment and their meanings are as follows:

[0039] The ratio of the carboxylic acid group and the sulfonic acid or phosphoric acid group on the surface of the semipermeable membrane of the present invention is determined by X-ray photoelectron spectroscopy (XPS). The specific method is: the surface of the modified active layer of the membrane sample is scanned and measured by an XPS spectrometer to obtain the XPS spectrum of the sample; the C element peak near 284eV and the S element peak near 162eV or the P element peak near 135eV are selected for narrow scanning, and the C element peak and the S element peak or the P element peak are calculated according to the chemical bond, and the ratio of the carboxyl group (denoted as C) and the ratio of the sulfonic acid and phosphoric acid groups (denoted as X) can be obtained, thereby obtaining the ratio of the carboxylic acid group to the sulfonic acid or phosphoric acid group (i.e., C / X). The smaller the C / X, the higher the amount of negatively charged groups introduced.

[0040] The surface negative charge density of the semipermeable membrane of the present invention is measured by toluidine blue dyeing method. The specific method is: the surface of the modified active layer of the membrane sample is dyed with a toluidine blue aqueous solution with a pH of 11, a circular sample of the dyed membrane with a radius of 1.5 cm is cut, and then the circular membrane sample is decolorized in a certain amount of aqueous solution with a pH of 2, and the decolorized solution is collected, and its concentration is tested by an ultraviolet spectrophotometer, and the negative charge density of the surface of the semipermeable membrane is calculated by the following formula.

[0041] Negative charge density on the surface of the semipermeable membrane (cells / nm 2 ) = (concentration of toluidine blue in the decolorizing solution × volume of the decolorizing solution × Avogadro constant) / area of ​​the circular membrane sample.

[0042] The pore size and pore size distribution of the semipermeable membrane modified active layer are observed and measured by super-resolution electron microscopy. The specific method is: embed the semipermeable membrane sample with epoxy resin, cut it with an ultrathin slicer to make ultrathin slices for easy observation of the cross section. For the obtained ultrathin slices, use a super-resolution electron microscope to take cross-sectional photos, observe and photograph the cross section of the modified active layer, and use image recognition to statistically calculate the average pore size A and pore size distribution of the modified active layer. Calculate the proportion of large pores with a pore size greater than 1.5 times the average pore size. The smaller the proportion, the more uniform the pore size distribution.

[0043] The test conditions of the membrane element in the embodiment are:

[0044] Magnesium sulfate removal rate: Evaluation water adjusted to a temperature of 25±1°C, pH 6.5-7.5, and a magnesium sulfate concentration of 2000 mg / L was supplied to the semipermeable membrane at an operating pressure of 70 PSI, and the conductivity of the supply water and the permeated water was measured using a conductivity meter to obtain the actual salinity, i.e., the magnesium sulfate concentration. The magnesium sulfate removal rate was calculated based on the magnesium sulfate concentration obtained and the following formula.

[0045] Magnesium sulfate removal rate (%)=[1-(magnesium sulfate concentration in permeate water) / (magnesium sulfate concentration in feed water)]×100.

[0046] Membrane permeation water volume: Evaluation water adjusted to 25°C, pH 7.0, and magnesium sulfate concentration of 2000 mg / L was supplied to the semipermeable membrane at an operating pressure of 70 PSI, and the membrane permeation water volume (L·m -2 ·h -1 ).

[0047] Comparative Example 1

[0048] Piperazine (PIP) and third-generation polypropyleneimine (PPI-G3) were added to pure water respectively to prepare an aqueous solution containing 3.0wt% PIP and 0.3wt% PPI-G3, which was contacted with a porous support layer. After removing excess water phase, it was reacted with an oil phase containing 0.25wt% trimesoyl chloride (TMC), and a semipermeable membrane was obtained after post-treatment.

[0049] Comparative Example 2

[0050] Piperazine (PIP) was added to pure water to prepare an aqueous solution containing 3.0 wt% PIP, which was contacted with a porous support layer. After removing the excess water phase, it was reacted with a n-hexane solution containing 0.25 wt% trimesoyl chloride (TMC) to obtain a primary active layer. The newly formed active layer was reacted with a 10 wt% 3-cyclohexylaminopropane sulfonic acid solution at 55°C, and a semipermeable membrane with a strong negative charge on the surface was prepared after post-treatment.

[0051] Example 1

[0052] Piperazine (PIP) and third-generation polypropylene imine (PPI-G3) were added to pure water to prepare an aqueous solution containing 3.0wt% PIP and 0.3wt% PPI-G3, which was contacted with a porous support layer, and after removing excess water phase, it was reacted with a n-hexane solution containing 0.25wt% trimesoyl chloride (TMC) to obtain a primary active layer. The primary active layer was reacted with a 10wt% 3-cyclohexylaminopropane sulfonic acid solution at 55°C to prepare a semipermeable membrane with a narrow pore size and pore size distribution and a strongly negatively charged surface.

[0053] Example 2

[0054] The film-making method of this embodiment is basically the same as that of Embodiment 1, except that the polyamine monomer used is polyethylene glycol diamine with a concentration of 3.0 wt %.

[0055] Example 3

[0056] Piperazine (PIP) and third-generation polyamidoamine (PAMAM-G3) were added to pure water to prepare an aqueous solution containing 3.0wt% PIP and 0.3wt% PAMAM-G3, which was contacted with a porous support layer, and after removing excess water phase, it was reacted with a n-hexane solution containing 0.25wt% trimesoyl chloride (TMC) to obtain a primary active layer. The primary active layer was reacted with a 10wt% 3-cyclohexylaminopropane sulfonic acid solution at 55°C to prepare a semipermeable membrane with a narrow pore size and pore size distribution and a strongly negatively charged surface.

[0057] Example 4

[0058] Piperazine (PIP) and third-generation polyamidoamine (PAMAM-G3) were added to pure water to prepare an aqueous solution containing 3.0wt% PIP and 0.01wt% PAMAM-G3, which was contacted with a porous support layer, and after removing excess water phase, it was reacted with a n-hexane solution containing 0.25wt% trimesoyl chloride (TMC) to obtain a primary active layer. The primary active layer was reacted with a 10wt% 3-amino-1-propanesulfonic acid solution at 55°C to prepare a semipermeable membrane with a narrow pore size and pore size distribution and a strongly negatively charged surface.

[0059] Example 5

[0060] The film-making method of this embodiment is substantially the same as that of embodiment 4, except that the concentration of the third-generation polyamidoamine (PAMAM-G3) is 0.1 wt %.

[0061] Example 6

[0062] The film-making method of this embodiment is substantially the same as that of embodiment 4, except that the concentration of the third-generation polyamidoamine (PAMAM-G3) is 0.3 wt %.

[0063] Example 7

[0064] The film-making method of this embodiment is substantially the same as that of embodiment 4, except that the concentration of the third-generation polyamidoamine (PAMAM-G3) is 0.5 wt %.

[0065] Example 8

[0066] The film-making method of this embodiment is substantially the same as that of embodiment 4, except that the concentration of the polyamine piperazine (PIP) is 0.1 wt %.

[0067] Example 9

[0068] Piperazine (PIP) and third-generation polyamidoamine (PAMAM-G3) were added to pure water to prepare an aqueous solution containing 3.0wt% PIP and 0.3wt% PAMAM-G3, which was contacted with a porous support layer, and after removing excess water phase, it was reacted with a n-hexane solution containing 0.25wt% trimesoyl chloride (TMC) to obtain a primary active layer. The primary active layer was reacted with a 15wt% 3-amino-1-propanesulfonic acid solution at 55°C to prepare a semipermeable membrane with a narrow pore size and pore size distribution and a strongly negatively charged surface.

[0069] Example 10

[0070] The membrane preparation method of this embodiment is substantially the same as that of embodiment 9, except that the concentration of 3-amino-1-propanesulfonic acid is 20 wt %.

[0071] Embodiment 11

[0072] The membrane preparation method of this embodiment is substantially the same as that of embodiment 9, except that the concentration of 3-amino-1-propanesulfonic acid is 30 wt %.

[0073] Example 12

[0074] The membrane preparation method of this embodiment is basically the same as that of Embodiment 9, except that the temperature at which the 3-amino-1-propanesulfonic acid solution reacts with the primary active layer is 65°C.

[0075] Embodiment 13

[0076] The membrane preparation method of this embodiment is basically the same as that of Embodiment 9, except that the temperature at which the 3-amino-1-propanesulfonic acid solution reacts with the primary active layer is 85°C.

[0077] The semipermeable membranes prepared in Comparative Examples 1-2 and Examples 1-13 were tested for their pore size distribution, the ratio of carboxyl groups to sulfonic acid groups or phosphoric acid groups on the membrane surface (C / X ratio), the density of negatively charged groups on the membrane surface, and the MgSO4 removal rate and flux. The results are summarized in Table 1.

[0078] Table 1

[0079]

[0080] It can be seen from the data in Table 1 that in Examples 1-13, compared with Comparative Examples 1 and 2, the pore size distribution of the semipermeable membrane is more uniform, the negative charge density on the membrane surface is also higher, and the removal rate of MgSO4 is significantly improved.

[0081] Specifically, it is found from Comparative Examples 1-2 and Example 1 that the semipermeable membrane prepared by adding only the dendritic polyamine compound or the compound having an amino group and at least one strongly negatively charged group has a relatively dispersed pore size distribution, the number of pores with a diameter greater than 1.5 times the average pore size exceeds 15%, the surface negative charge density is low, and the removal rate of MgSO4 is less than 98%. Only when the dendritic polyamine compound or the compound having an amino group and at least one strongly negatively charged group are added together, the pore size distribution of the semipermeable membrane becomes uniform due to the synergistic effect between the two, and the C / X ratio of the membrane surface is less than 1.5, indicating that more negatively charged groups are introduced, and the surface negative charge density reaches 28.6 / nm 2 , the removal rate and flux of MgSO4 were significantly improved.

[0082] It can be seen from Examples 1 and 2 that Example 1 using piperazine has better pore size uniformity, higher negative charge density, and higher MgSO4 removal rate and flux than Example 2 using polyethanol diamine. This indicates that the semipermeable membrane prepared with piperazine has fewer defects.

[0083] It can be seen from Examples 1 and 3 that the semipermeable membrane prepared by using polyamidoamine as the dendritic polyamine molecule has a higher uniformity of pore size distribution, a higher negative charge density on the membrane surface, and a higher removal rate of MgSO4. This is because the structure of polyamidoamine is close to spherical, and the effect of emulsification and regulating interfacial polymerization reaction is better.

[0084] By comparing Examples 4-6, it can be seen that when the concentration of the added dendritic polyamine compound polyamidoamine is less than or equal to 10% of the polyamine concentration, the higher the concentration of polyamidoamine, the higher the pore size distribution uniformity of the semipermeable membrane, the negative charge density of the membrane surface, and the removal rate of MgSO4. By comparing Examples 6 and 7, it can be seen that when the addition amount of polyamidoamine is greater than 10% of the polyamine concentration, the pore size uniformity of the semipermeable membrane will decrease, and the MgSO4 removal rate will decrease significantly, because the addition of excessive dendritic polyamine compounds destroys the structure of the active layer.

[0085] It can be seen from Examples 3 and 6 that the semipermeable membrane prepared using 3-amino-1-propanesulfonic acid has a more uniform pore size distribution, a higher load electrical density on the membrane surface, and a higher removal rate of MgSO4.

[0086] It can be seen from Examples 4 and 8 that when the content of polyamine piperazine (PIP) is too low, the macropore content in its pore size distribution increases. Although the flux increases, the negative charge density on the membrane surface decreases and the removal rate of MgSO4 also decreases to a certain extent.

[0087] It can be seen from Examples 6 and 9-11 that increasing the concentration of 3-amino-1-propanesulfonic acid can significantly improve the pore size distribution uniformity, membrane surface negative charge density and MgSO4 removal rate of the semipermeable membrane. However, when the concentration of 3-amino-1-propanesulfonic acid is greater than 20wt%, the further improvement of the performance of the semipermeable membrane is minimal.

[0088] It can be seen from Examples 9, 12 and 13 that increasing the temperature of the reaction between 3-amino-1-propanesulfonic acid and the primary active layer can also improve the pore size distribution uniformity of the semipermeable membrane, the negative charge density of the membrane surface and the removal rate of MgSO4. Generally speaking, a temperature higher than 85°C will damage the active layer, so the reaction temperature should not be too high.

[0089] The positive electrode material of the ternary battery was dissolved by acid to prepare a positive electrode material solution with a TDS of 20 g, and the solution was used to test the separation constants of lithium and nickel cobalt manganese (Li / (Ni+Co+Mn)) of the semipermeable membranes obtained in Comparative Examples 1 and 2 and Examples 1-13.

[0090] Li / (Ni+Co+Mn) separation constant: The temperature was adjusted to 25±1°C and the above cathode material solution was supplied to the semipermeable membrane at an operating pressure of 70 PSI. The metal ion types and concentrations of the supplied water and the permeated water were measured using an inductively coupled plasma spectrometer (ICP) to obtain the concentrations of various ions. Based on the concentrations of each ion obtained and the following formula, the Li / (Ni+Co+Mn) separation constant was calculated.

[0091] Li / (Ni+Co+Mn) separation constant = (permeate water Li concentration / supply water Li concentration) / (permeate water Ni+Co+Mn concentration / supply water Ni+Co+Mn concentration)

[0092] The Li / (Ni+Co+Mn) separation constants of the semipermeable membranes prepared in Comparative Examples 1-2 and Examples 1-13 were tested, and the results are summarized in Table 2.

[0093] Table 2

[0094]

[0095] From the data in Table 2, it can be seen that compared with Comparative Examples 1 and 2, the Li / (Ni+Co+Mn) separation constant of the semipermeable membrane obtained in Examples 1-13 is significantly improved, and has a high efficiency of Li / (Ni+Co+Mn) ion separation ability. It can be seen that when the dendritic polyamine compound and the molecule containing an amino group and at least one strongly negatively charged group are added together, the prepared semipermeable membrane has a high efficiency of Li / (Ni+Co+Mn) ion separation ability. At the same time, the Li / (Ni+Co+Mn) separation constant of the combination of polyamide amine and 3-amino-1-propanesulfonic acid is higher. At the same time, when the polyamide concentration is 0.3wt%, the 3-amino-1-propanesulfonic acid concentration is 15wt% and the reaction temperature is 85°C, the Li / (Ni+Co+Mn) separation constant can reach more than 600, showing a better selective separation.

[0096] Industrial Applicability

[0097] The semipermeable membrane provided by the present invention has good metal ion selective separation due to its uniform pore size distribution of the modified active layer and high surface negative charge density. When applied to the field of waste battery recycling, it can efficiently separate monovalent lithium ions and multivalent metal ions such as nickel, cobalt and manganese in the battery positive electrode solution to achieve green battery recycling. At the same time, due to the large number of hydrophilic groups on its surface, it can reduce membrane pollution and improve system stability.

Claims

1. A semipermeable membrane comprising a porous support layer and a modified active layer disposed on the porous support layer, characterized in that: The modified active layer comprises a primary layer containing a dendritic polyamine compound, polyamines, and polyacyl chlorides, and a negatively charged layer containing a strong negatively charged group formed on the primary layer.

2. The semipermeable membrane according to claim 1, characterized in that: The dendritic polyamine compound is one or more of polyamidoamine, polylysine or polypropyleneimine.

3. The semipermeable membrane according to claim 1, characterized in that: The negatively charged layer is obtained by reacting a primary layer with a compound containing an amino group and at least one of the strongly negatively charged groups.

4. The semipermeable membrane according to claim 1, characterized in that: The compound containing an amino group and at least one strongly negatively charged group is a small molecule compound containing at least one amino group connected to a carbon atom and at least one strongly negatively charged group.

5. The semipermeable membrane according to claim 4, characterized in that: The small molecule compound containing at least one amino group connected to a carbon atom and at least one of the strongly negatively charged groups is a compound having the following chemical formula: R a (CH n ) b NH m , wherein R is the strong negatively charged group, the strong negatively charged group is a sulfonic acid group or a phosphoric acid group; a is any integer from 1 to 3, b is any integer from 1 to 10, n is any integer from 0 to 2, and m is any integer from 1 to 2.

6. The semipermeable membrane according to claim 1, characterized in that: The average pore size of the modified active layer is A, and the proportion of pores with a pore size greater than 1.5A is ≤15%.

7. The semipermeable membrane according to claim 1, characterized in that: The surface of the modified active layer contains carboxyl groups, and the relationship between the number C of the carboxyl groups and the total amount X of the strongly negatively charged groups is C / X≤1.

5.

8. The semipermeable membrane according to claim 1, characterized in that: The surface negative charge group density of the modified active layer is ≥ 20 / nm -2 .

9. The method for preparing a semipermeable membrane according to any one of claims 1 to 8, characterized in that: It includes the following steps: (1) contacting the porous support layer with an aqueous solution containing a dendritic polyamine compound and a polyamine monomer, and then contacting the porous support layer with an oil solution containing a polyacid chloride to form a primary layer on the porous support layer; (2) The primary layer is contacted with a solution of a compound containing an amino group and at least one strongly negatively charged group to obtain a semipermeable membrane containing a modified active layer.

10. The method for preparing a semipermeable membrane according to claim 9, characterized in that: The mass concentration of the dendritic polyamine compound in the aqueous phase solution is less than or equal to 10% of the mass concentration of the polyamine monomer.

11. The method for preparing a semipermeable membrane according to claim 9, wherein: The compound containing an amino group and at least one strongly negatively charged group is a small molecule compound containing at least one amino group connected to a carbon atom and the strongly negatively charged group.

12. The method for preparing a semipermeable membrane according to claim 11, wherein: The small molecule compound containing at least one amino group connected to a carbon atom and at least one of the strongly negatively charged groups is a compound having the following chemical formula: R a (CH n ) b NH m , wherein R is the strong negatively charged group, the strong negatively charged group is a sulfonic acid group or a phosphoric acid group; a is any integer from 1 to 3, b is any integer from 1 to 10, n is any integer from 0 to 2, and m is any integer from 1 to 2.

13. The method for preparing a semipermeable membrane according to claim 9, characterized in that: The mass concentration of the compound solution containing an amino group and at least one of the strongly negatively charged groups is ≤20 wt %.

14. The preparation method according to claim 9, characterized in that: The reaction temperature when the solution of the compound containing an amino group and at least one strongly negatively charged group contacts the primary layer is 20°C to 85°C.

15. Use of the semipermeable membrane according to any one of claims 1 to 8 in recycling positive electrode materials of batteries.